Structural characteristics and antioxidant activity of a low-molecular-weight jujube polysaccharide by ultrasound assisted metal-free Fenton reaction - Yingying Liu; Yan Meng; Haozhen Ji; Jianhang Guo; Miaomiao Shi; Feiliao Lai; Xiaolong Ji (Food Chemistry: X, 2024)
This study used an ultrasonically accelerated metal-free Fenton (H2O2-Vc system) reaction to promote water-extracted degrading polysaccharides from Ziziphus Jujuba cv. Muzao (DZMP). A novel jujube polysaccharide (DPZMP3) was obtained by degradation using DEAE-Sepharose Fast Flow and Sephacryl S-100 column chromatography. Methylation analysis, HPGPC, ion chromatography, FT-IR, and NMR spectroscopies were used to clarify the chemical structures of DPZMP3. Monosaccharide compositional analysis of DPZMP3 revealed the presence of Rha, Ara, Gal, and GalA at a molar ratio of 1.00:1.49:1.60:7.68, and the HPGPC data demonstrated the average Mw of 34.3 kDa. Based on the structural and linkage research using NMR spectroscopy and GC–MS, it was determined that DPZMP3 was a homogalacturonan pectic polysaccharide with a (1 → 4)-Galp branch at C-6 and a small amount of Araf and Rhap residues. The ultrasonic-aided Fenton treatment did not significantly alter the structure of DPZMP3. It may also be useful for DZMP and enhancing their antioxidant activity in vitro. The current study's findings could pave the way for the food sector to use jujube polysaccharides obtained by degradation as a functional food component.